Lifetime Amelioration of Release-Agent-Free Antireflection-Structured Replica Molds by Partial-Filling Ultraviolet Nanoimprint Lithography - Nurhafizah, Abu Talip; Hayashi, Tatsuya; Taniguchi, Jun; Hiwasa, Shin (IOP Publishing, 2015)

(untitled)
In ultraviolet nanoimprint lithography (UV-NIL), the presence of fluorinated components in a release-agent-free antireflection-structured (RAF-ARS) replica mold is an important factor preventing the adhesion of resin on its surface. Nevertheless, a strong release force (RF), which results from the complete filling of resin in a high-aspect-ratio RAF-ARS replica mold during UV-NIL, degrades its fluorinated components and consequently shortens its lifetime. In this paper, we propose a technique for the lifetime amelioration of RAF-ARS replica molds by partial-filling UV-NIL. Complete-filling UV-NIL was also executed for comparison. We also examined the effects of the filling ratio on an RAF-ARS replica mold. Using the partial-filling UV-NIL technique, we successfully prolonged the lifetime of an RAF-ARS replica mold up to the 100th imprint, compared with the 75th imprint in the case of complete-filling UV-NIL.